2015
DOI: 10.1159/000441788
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Outcome of Infertile Patients with Fibroids Based on the Patient and Fibroid Characteristics; Optimal and Personalized Management

Abstract: Aims: To analyze the detailed clinical course of infertile patients with uterine fibroids and to identify optimal and personalized treatment based on the patient or fibroid characteristics. Methods: Retrospective analysis of a case series was performed on 176 infertile patients with fibroids. The patients were classified into different groups according to different treatments (conservative infertility treatment, myomectomy and non-myomectomy surgery). Patient or fibroid characteristics for different groups wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…67 Forty-one percent of patients who underwent GnRH agonist followed by myomectomy in one study were able to become pregnant, and they had previously been unable to conceive for an average of 4 years prior to the surgery. 68 Studies have found that myomectomy is beneficial for patients with fibroids who fail conservative infertility treatments, 69 or when fibroids are the only attributable cause of infertility. 70,71 The cumulative rate of pregnancy over a 2-year period in women younger than 30 years who had undergone abdominal myomectomy was 87% in one study, with decreasing probability with increasing age after 30 years.…”
Section: Abdominal (Open) Myomectomymentioning
confidence: 99%
“…67 Forty-one percent of patients who underwent GnRH agonist followed by myomectomy in one study were able to become pregnant, and they had previously been unable to conceive for an average of 4 years prior to the surgery. 68 Studies have found that myomectomy is beneficial for patients with fibroids who fail conservative infertility treatments, 69 or when fibroids are the only attributable cause of infertility. 70,71 The cumulative rate of pregnancy over a 2-year period in women younger than 30 years who had undergone abdominal myomectomy was 87% in one study, with decreasing probability with increasing age after 30 years.…”
Section: Abdominal (Open) Myomectomymentioning
confidence: 99%
“…More over the determinants that had a substantial impact on the out come of the surgery were independent of the treatment (i.e. age, infertility and presence of additional but treatable in fertility factors on the other hand the cumulative pregnancy rate of the population studied is well above that observe in couples with un-explained infertility who are followed up without treatment 6,7 . The study findings were consistent with other studies 8,9 .…”
Section: Discussionmentioning
confidence: 91%
“…Due to location of fibroids in the uterine cavity it is also associated with recurrent abortions 6 . Myomectomy procedure increase the chances of pregnancy and decreases the rate of spontaneous miscarriage in many studies 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes there is improvement in the obstetric situation in women with recurrent miscarriage, or a history of early delivery after conservative myomectomy. Conservative myomectomy improves the obstetric prognosis of subsequent pregnancies [33][34][35]. Considering loss of pregnancy, submucous fibroids are associated with a higher frequency of miscarriages, possibly due to deformation of the uterine cavity, impaired endometrial function, and placentation disorders [36,37].…”
Section: Resultsmentioning
confidence: 99%